Model Kesetimbangan Adsorpsi Doxorubicin Pada Hidroksiapatit - Muhammad Hamdani; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite has been applied in the biomedical field as drug delivery. The drug will be absorbed onto the hydroxyapatite surface through the adsorption process. The purpose of this study was to determine the effect of initial concentration of doxorubicin (DOX) and the operating temperature on hydroxyapatite adsorption, and to determine the appropriate adsorption equilibrium model. Research began by making a solution of doxorubicin with an initial concentration of 485.83; 661.67; 884.17 mg/L. A 5 mL DOX solution was mixed with 10 mg hydroxyapatite in a beaker glass, then stirred using a magnetic stirrer at 220 rpm at 30, 40, 50 °C for 18 hours. After centrifugation, the concentration of DOX solution in the liquid was tested using UV-Vis spektofotometry. The results showed that the adsorption capacity () increased with increasing initial concentration () DOX. The value of () increased consecutively from 223.86-430.18; 231.59-434.46; 230.48-432.04 mg/g with increasing ofvalue from 485.83-884.17 mg/L at temperature of 30, 40, 50 °C. The highest value of () was obtained at 40 °C, i.e., 231.59-434.46 mg/g. It was found that the Langmuir was an appropriate equilibrium model, where the maximum adsorption capacity () values for each temperature 30, 40, 50 °C are 151.52; 163.93; 181.82 mg/g.Keywords: adsorption, doxorubicin, equilibrium model, hydroxyapatite.